Integrative systematics with structural monophyly and ancestral signatures: Chionoloma (Bryophyta) - Richard Zander (Academia Biology)
The moss genus Chionoloma (Pottiaceae, Bryophyta), recently presented in a molecular analysis as a massive genus inflated by the synonymy of several heretofore accepted genera, is deframed and reformatted to internally define minimally monophyletic genera. This resurrects from the molecular synonymy of the genera Oxystegus and Pseudosymblepharis. Morphologically determined evolutionary relationships of species are combined with molecular signatures of ancestral species to devise an integrated evolutionary classification for the group. The methods include second-order morphological Markov chains, Shannon–Turing sequential Bayes statistical support, and multi-node molecular evidence of ancestry. This study is based on data and revisionary results from the original studies by other authors and from the study of herbarium specimens of authentic material. The reframing of this portmanteau genus directly affects the apprehension of biodiversity and rescues two genera from epistemological extinction.